Physical Properties of Toothpaste Base Formulations - Karen Sofiana; Octarina; Florencia Livia Kurniawan; Gladys Mawarni Siregar; Fathilah Abdul Rajak (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Dental caries is a prevalent oral disease resulting from enamel demineralization caused by acidogenic bacterial activity. Toothpaste plays an important role in caries prevention through a combination of ingredients such as calcium carbonate, sorbitol, glycerin, gum arabic, sodium carboxymethyl cellulose, sodium fluoride, citric acid, and peppermint oil. This study aimed to evaluate the physicochemical properties of an experimental toothpaste base formulation. Material and Methods: This study employed a laboratory-based experimental design with a descriptive observational approach. The physicochemical properties, including pH, viscosity, and homogeneity, were evaluated on a toothpaste base formulation and compared with a commercially available toothpaste. Results and Discussion: Both the toothpaste base formulation and the commercial toothpaste exhibited pH values within the range of 7.80–7.85, meeting the requirements of the Indonesian National Standard (SNI). The toothpaste base formulation demonstrated a substantially lower viscosity (56.232 cP)  compared to the commercial toothpaste (182.872 cP). Differences in viscosity may be attributed to variations in formulation composition and thickening agents. Homogeneity testing confirmed that both formulations were physically homogeneous, indicating uniform distribution of ingredients and acceptable physical stability. Conclusion: The toothpaste base formulation met the evaluated physical parameters and exhibited characteristics comparable to those of a commercial toothpaste. Although its viscosity was lower than that of the commercial product, it remained within the range commonly reported for toothpaste formulations. Further optimization of the formulation, particularly its rheological properties, is warranted to improve product performance and consumer acceptability.